Social exclusion lowers working memory capacity in gay‐men but not in heterosexual‐men. Issue 3 (1st April 2020) - Paolini, Daniele; Giacomantonio, Mauro; van Beest, Ilja; Baiocco, Roberto; Salvati, Marco
Summary: Because sexual orientation is a crucial factor in social discrimination, this study assessed how the working memory capacity of gay‐men and heterosexual‐men is affected by a social exclusion event ( N = 88). To manipulate the experience of social exclusion participants were included or excluded from a game of Cyberball. To assess working memory capacity, participants had to recall a series of letters while performing math problems in an automated version of the operation span task. The results of this small study, showed the sexual orientation of participants interacted with variations in belonging such that being ostracized (but not being included) lowered the working memory capacity of gay‐men relative to heterosexual‐men. Implications for research on belonging, social exclusion, and stereotype threat are discussed.